Resistance against HIV-1: role of chemokine receptor, CCR5 and restriction factor, APOBEC3G - ARSHIA BERRY; SAKSHI GUPTA; DR NAVKIRAN KAUR (International Journal of Pharma and Bio Sciences, 2017)
It can be rightly said that no one is really or truly “immune” from HIV/AIDS, however, there are a few individuals, around 1% of the world’s total population who exhibit strong natural resistance against the virus. Scientists have discovered two different types of adaptations against HIV in human population: one, which is able to repel the virus itself and the infection and the second that is able to keep HIV from giving way to AIDS. Chemokine binding co-receptor, CCR5 and endogenous anti-retroviral protein, APOBEC3G has been well studied individually in controlling the viral infection. However, the role of these proteins cumulatively remains controversial and opens new research opportunities to find out how these proteins are capable of inculcating minute genome differences in some people together in order to achieve natural resistance from HIV-1.